Shipping sustainability: black carbon, the next frontier and maritime shipping - environmental impacts (the future fuel for the shipping industry) - Bee, Man Jia (Nanyang Technological University, 2022)
The shipping industry is an integral part of global trade, accounting for more than four-fifths of worldwide merchandise trade by volume. With increasing economic growth and resounding desire for shipping sustainability, the spotlight is on the environmental impacts of the shipping industry. By 2050, the shipping industry is expected to decarbonize by at least 50% from 2008 levels. This emphasises the need to reduce both Long-Lived Climate Pollutants and Short-Lived Climate Pollutants to meet shipping sustainability goals. Alternative fuels are the next frontier of sustainable shipping where the possibility of zero emissions paves the way for a green shipping industry in the near future.